ULTRASONICATION ASSISTED EXTRACTION OF PHENOLIC ANTIOXIDANTS FROM CITRUS MAXIMA LEAVES AND THEIR GC-MS PROFILE - ABHILASHA SHOURIE (International Journal of Pharma and Bio Sciences, 2014)
Citrus maxima is a medicinally important plant used traditionally for protection against many diseases. Extraction of its phenolic content has been a subject of interest due to its wide range of biological effects like anti-oxidative, anti-inflammatory, anti-tumor and antimicrobial activities. The aim of the current research was to evaluate the novel ultrasonic assisted method for efficient extraction of antioxidant phenolic compounds from this plant. The extracts obtained through this method at different extraction times (15, 30, 45, 60 and 75 minutes) were estimated for 1, 1-diphenyl-2-picrylhydrazyl free radical scavenging activity, reduction potential and total phenolic contents. The extracts obtained through ultrasonication for 60 minutes exhibited highest anti-radical activity (79.21%), highest reduction potential (OD=1.24) and maximum total phenolic content (11.6 mg gallic acid equivalent per gram dry weight). Correlation analysis showed that there was a strong positive correlation between total phenolic content and anti-oxidant activities and the Gas Chromatography Mass Spectrometry analysis of the extracts revealed the presence of many pharmaceutically active compounds. It can therefore be concluded that UAE can be considered as a time saving method for efficient extraction of phenolic compounds from this plant.